Thrive - Oppel, Kenneth, 1967- (Oppel, Kenneth, 1967- Overthrow ;, 2021)
After the aliens begin their invasion of Earth, a rebel faction contacts Anaya and proposes a plan that would allow humans, hybrids, and cryptogens to coexist peacefully, though it is unclear if all hybrids will agree.